Predicting the annual escalator energy consumption based on short-term measurements. (September 2017) - Uimonen, Semen; Tukia, Toni; Siikonen, Marja-Liisa; Lehtonen, Matti
Abstract: This article presents a novel approach for the annual energy consumption estimation in escalator technology. The method is based on short-term energy measurements of several day types within a week. It suits best for appliances where the passenger flow is weekly recurring. This article explores the implication of the method with seasonal changes, as well as stresses the impact of various day types and holidays on annual energy consumption estimation. The performance of the proposed method was compared with the existing approaches of energy consumption estimation in the standard ISO 25745-3 and annual energy measurement results. The approach is favorable among other existing approaches because it does not require additional passenger measurements, while providing more accurate results.